The Intersection of CSR, Contextual Factors, and Executive Incentives - Höhre, Andreas; Justus Liebig University Giessen (My University, 2024)
This dissertation consists of three essays, each exploring how corporate social responsibility (CSR) is operationalized in businesses through the application of environmental, social, and governance (ESG) criteria. Across these essays, CSR and executive incentives are analyzed from multiple perspectives.
Keywords: CSR; ESG; Executive Incentives; ddc:330